The common dental diagnosis under general anaesthesia in Hospital Universiti Sains Malaysia: A four years paediatric case study - Samsudin, Norsamsu Arni; W Ahmad, Wan Muhamad Amir; M. Nashir, Muhamad Najib; Awang Nawi, Mohamad Arif; Mohd Ibrahim, Mohamad Shafiq; Aleng, Nor Azlida; Mohamad Ghazali, Farah Muna; Nizam Akbar, Nurul Asyikin; Mohd Noor, Nor Farid; Ghazali, Puspa Liza; Abdul Rahman, Nuzlinda (Sapporo Ika Daigaku, 2021)
Dental treatment under general anaesthesia (GA) is often indicated in uncooperative paediatric patients with or without the complex dental procedure. Preoperative diagnosis needs to be thoroughly assessed to ensure the dental treatment under GA can be efficient and safely completed by the paediatric dentist and trained anaesthetist. The research aims to determine the common preoperative diagnosis prior dental treatment under GA among paediatric patients in Hospital UniversitiSains Malaysia, and its association to gender. A retrospective review of paediatric dental treatment under GA from 2015 to 2018 was undertaken. A total of 298 patient’s records were retrieved for data collection. Descriptive statistics and multiple response analysis were used to analyze the data. The most common preoperative diagnosis made was early childhood caries (53.1%, n=188), followed by dental caries (25.1%) and dentoalveolar abscess (17.1%). Firstly, the analysis of multiple responses was combined between male and female; the highest diagnosis within four years was ECC diagnosis 188(53.1%) and dental caries 89(25.1%). Second, the result was being separate according to gender. The result indicates that the ECC diagnosis for males; 98(52.7%) and females; 90(53.6%), while dental caries is 49(26.3%) for males and 40(23.8%) for females. This research is beneficial for the better understanding the paediatric dental service, particularly those children who are indicated for dental treatment under GA.